Curricular Adaptations: Similarities and Differences of their Implementation in Chilean Faculty - Navarro-Aburto, Braulio Ademir (2016)
This research describes the process that is performed to carry out curriculum adaptations in the mathematics course for students who showed some type of temporary special education need. The existing coordination between mathematics and special needs’ teachers, as promoter action of the curricular adaptations, has been considered. The methodology used relates to qualitative with a phenomenological approach, and the main data collection technique was the semi-structured interview. In this study, ten teachers of two educational institutions featuring an integration program participated. The main findings show that faculty and responsible staff of the School Integration Program comply with the regulations and requirements of the Decree # 170  in relation to curricular adaptations, but such compliance is subject to informality in the articulation and planning due to lack of time and resources available. Therefore, it is concluded that there is a constant need for curriculum adaptations since these are a mechanism which allows the individualization of education, improving quality of life and special education in Chile